Agglomeration of iron ores - Bhagat, Ram Pravesh (Boca Raton : CRC Press, Taylor & Francis, 2019)
This book focuses on agglomeration, or the size enlargement process, of iron ores. This process sits at the interface of mineral processing and extractive metallurgy. The book begins with a discussion of raw materials preparation and the beneficiation process. It then describes fundamental principles of the sintering and pelletization processes, including formation of green mix through granulation and green balls as well as chemical reactions during sintering. Finally, it offers a brief description of iron making processes and correlations related to the agglomerates: quality parameters and BF productivity and coke rate.
3.5.2. Solution Loss Reaction and Shaft Efficiency3.6. Blast Furnace Performance: Factors Affecting; 3.6.1. Chemical Composition of Burden Materials; 3.6.2. Blast Furnace Burden; 3.6.3. Size of Burden Materials and its Distribution; 3.6.4. Cold Strength and Reduction Parameters of Agglomerates; 3.6.5. Permeability of the Stack Zone; 3.6.6. Permeability in Cohesive Zone; 3.6.7. Formation of Slag and its Characteristics; References; Chapter 4: Agglomerates in Iron-Making Processes; 4.1. Preamble; 4.2. Agglomerates in Iron-Making Processes; 4.2.1. Iron Ore Pellets in Direct Reduction (DR)
OCLC-licensed vendor bibliographic record.
Keywords: Iron ores; Ore-dressing.; Agglomeration; TECHNOLOGY / Material Science; TECHNOLOGY / Metallurgy